English informal language learning through social networking sites among Malaysian university students / Izaham Shah Ismail and Nurul Hidayu Shafie. - Ismail, Izaham Shah; Shafie, Nurul Hidayu (2018)
The use of ICT in education has benefitted both students and educators in the education field. Currently, the social networking sites are being used widely by the university students in their daily lives for various purposes such as entertainment, networking, as well as education purposes. There are many studies conducted to figure out whether the social networking sites benefit the students in formal education but there are not many studies done to investigate whether they are beneficial to students’ informal learning, especially in English language. Therefore, this study aims to investigate the contribution of the social networking sites to the university students' English informal language learning. This quantitative study was conducted on Malaysian public university students in Selangor and Negeri Sembilan. A descriptive quantitative survey research was conducted in order to answer the research questions of this study. The results of this study revealed that most of the respondents learned English informally by saving interesting English quotes or images posted on social networking sites as well as by paying attention to the sentence patterns and accent while watching videos on those sites. The respondents of this study also perceived that they informally learned listening skills and vocabulary the most from the social networking sites. To conclude, the social networking sites are not only useful for entertaining purposes, they could also be used to informally learn and improve one’s English language skills.